2021
DOI: 10.1038/s41374-020-00485-2
|View full text |Cite|
|
Sign up to set email alerts
|

Ascorbate-induced oxidative stress mediates TRP channel activation and cytotoxicity in human etoposide-sensitive and -resistant retinoblastoma cells

Abstract: There are indications that pharmacological doses of ascorbate (Asc) used as an adjuvant improve the chemotherapeutic management of cancer. This favorable outcome stems from its cytotoxic effects due to prooxidative mechanisms. Since regulation of intracellular Ca2+ levels contributes to the maintenance of cell viability, we hypothesized that one of the effects of Asc includes disrupting regulation of intracellular Ca2+ homeostasis. Accordingly, we determined if Asc induced intracellular Ca2+ influx through act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 113 publications
(160 reference statements)
0
18
0
Order By: Relevance
“…The etoposide sensitive and resistant RB cell lines WERI RB1 and WERI ETOR were cultivated as previously described (13)(14)(15)(16)(17). The identities of these RB cell lines were verified by DNA fingerprinting and profiling using eight different and highly polymorphic short tandem repeat (STR) loci (Leibniz-Institute DSMZ GmbH, Braunschweig, Germany).…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…The etoposide sensitive and resistant RB cell lines WERI RB1 and WERI ETOR were cultivated as previously described (13)(14)(15)(16)(17). The identities of these RB cell lines were verified by DNA fingerprinting and profiling using eight different and highly polymorphic short tandem repeat (STR) loci (Leibniz-Institute DSMZ GmbH, Braunschweig, Germany).…”
Section: Cell Culturementioning
confidence: 99%
“…Furthermore, Busch et al demonstrated a higher proliferation rate in WERI ETOR as well as an increased tumor formation and tumor size in an in vivo chick chorioallantoic membrane assay (17). Mergler et al and Oronowicz et al showed alterations in thermosensitive transient receptor potential channels in WERI ETOR cells (13,16). A publication by Kakkassery et al proved an upregulation of sphingosine-1-phosphate in the WERI ETOR cell line as a potential resistance mechanism in RB (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the mechanisms of chemotherapy resistance, the etoposide-resistant subclone WERI-ETOR was established by harvesting surviving cells after incubation with increasing etoposide doses from WERI-RB1, as described by Stephan et al [ 12 ]. Previous studies also examined the parental WERI-RB1 and the etoposide-resistant subclone WERI-ETOR on the molecular level [ 13 , 14 , 15 , 16 , 17 , 18 ]. Furthermore, Busch et al demonstrated a higher proliferation rate in WERI-ETOR as well as increased tumor formation and tumor size in an in vivo chick chorioallantoic-membrane assay [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Soluble guanylyl cyclase, a messenger that can decrease collagen production and Ca 2+ entry, is highly expressed in RA tissues but markedly reduced or absent in LA tissues [ 18 , 19 , 20 ]. Compared with RA fibroblasts, LA fibroblasts produce a higher level of oxidative stress, which has been found to induce Ca 2+ entry [ 13 , 21 ]. Increased intracellular Ca 2+ is mainly derived either from extracellular Ca 2+ entry or from endoplasmic reticulum (ER) Ca 2+ release.…”
Section: Introductionmentioning
confidence: 99%